2007
DOI: 10.1016/j.genhosppsych.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Older primary care patients' willingness to consider discontinuation of chronic benzodiazepines

Abstract: Objective-To examine factors related to older primary care patients' willingness to consider tapering/discontinuation of long-term benzodiazepine use.Method-Forty-six long-term anxiolytic benzodiazepine users, aged 61-95 years, were assessed over the telephone using a semi-structured qualitative interview and standardized self-report questionnaires for anxiety (Beck Anxiety Inventory), sleep quality (Pittsburgh Sleep Quality Index), depression (Center for Epidemiological Studies Depression Scale), psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Of note, additional screening measures in a group of Philadelphia primary care clinics observed that those patients with lower frequency of use and less anxiety were more likely to be willing to engage in tapering or discontinuing their benzodiazepine use. 41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, additional screening measures in a group of Philadelphia primary care clinics observed that those patients with lower frequency of use and less anxiety were more likely to be willing to engage in tapering or discontinuing their benzodiazepine use. 41 …”
Section: Discussionmentioning
confidence: 99%
“…While these studies did not meet criteria for this review, they may provide ideas for formulating research and interventions related to older adults and prescription medication misuse. 7,13,15,38,4147,50,5765 …”
Section: Discussionmentioning
confidence: 99%
“…An assessment procedure based on self-rated addiction also might help nurses uncover potential substance dependence. Developing this knowledge is essential for nurses because clinicians tend to overlook BZD dependence among the elderly (Voyer, Cappeliez, Pérodeau, & Préville, 2005;Voyer, Cohen, Lauzon, & Collin, 2004b;Voyer & Schindel-Martin, 2003), downplay its clinical significance (Anthierens et al, 2007;Cook, Marshall, Masci, & Coyne, 2007;Damestoy, Collin, & Lalande, 1999), fail to identify its presence or do not discuss the issue with their patients despite their being aware of the risk of dependence (Anthierens et al, 2007;Cook, Biyanova, Masci et al, 2007;Cook, Biyanova, Thompson, & Coyne, 2007;Pimlott et al, 2003). Asking a single, simple and direct question of older adults such as: "Do you think you are dependent on your BZD" is easy to administer, and recent studies and various scales have supported the clinical relevance of doing so.…”
Section: The Study Of Feeling Addictedmentioning
confidence: 99%
“…As pointed out by a qualitative study in 50 users aged 61-95 years [18,19], many depend on BZDs for their unique soothing effects, and denied and minimized side effects. They showed reluctance to discontinue or taper the medication down, fearing suffering without it, and perceived such a measure an arduous, low priority and time-intensive task.…”
Section: Do Older Patients Have Higher Risks?mentioning
confidence: 99%